Vasculoprotective Effects of Vildagliptin. Focus on Atherogenesis - Michał Wiciński (International Journal of Molecular Sciences, 2020)
Vildagliptin is a representative of Dipeptidyl Peptidase-4 (DPP-4) inhibitors, antihyperglycemic drugs, approved for use as monotherapy and combination therapy in type 2 diabetes mellitus. By inhibiting enzymatic decomposition, DPP-4 inhibitors increase the half-life of incretins such as GLP-1 (Glucagon-like peptide-1) and GIP (Gastric inhibitors polypeptide) and prolong their action. Some studies present results suggesting the anti-sclerotic and vasculoprotective effects of vildagliptin reaching beyond glycemic control. Vildagliptin is able to limit inflammation by suppression of the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling pathway and proinflammatory agents such as TNF-α (tumor necrosis factor α), IL-1β (Interleukin-1β), and IL-8 (Interleukin 8). Moreover, vildagliptin regulates lipid metabolism; attenuates postprandial hypertriglyceridemia; and lowers serum triglycerides, apolipoprotein B, and blood total cholesterol levels. This DPP-4 inhibitor also reduces macrophage foam cell formation, which plays a key role in atheromatous plaque formation and stability. Vildagliptin reduces vascular stiffness via elevation of nitric oxide synthesis, improves vascular relaxation, and results in reduction in both systolic and diastolic blood pressure. Treatment with vildagliptin lowers the level of PAI-1 presenting possible antithrombotic effect. By affecting the endothelium, inflammation, and lipid metabolism, vildagliptin may affect the development of atherosclerosis at its various stages. The article presents a summary of the studies assessing vasculoprotective effects of vildagliptin with special emphasis on atherogenesis.